2022
DOI: 10.1007/s00281-022-00912-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease involving symmetric joints and is generally characterized by persistent pain, tenderness, and destruction of joints. The vast majority of RA patients produce autoantibodies, and immune cell involvement in disease development is well recognized, as is the contribution of other types of cells in synovial tissue, like fibroblasts. It is known that there are major genetic associations with the HLA locus, while multiple non-HLA genetic variants display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 90 publications
(109 reference statements)
0
52
0
3
Order By: Relevance
“…Genetic association estimates for seropositive and seronegative RA were taken from a published study of RA (21) that reported separate genome-wide association studies (GWAS) of seropositive (18,019 cases and 991,604 controls) and seronegative (8,515 cases and 1,015,471 controls) RA. One hundred and thirty-five autosomal single nucleotide polymorphisms (SNPs) that were associated with RA (either seropositive, seronegative or both) in previous GWAS of European ancestry or multi-ancestry were selected as IVs for RA (22). These IVs were used for testing the causal effect of RA as the exposure and on IPF as the outcome.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic association estimates for seropositive and seronegative RA were taken from a published study of RA (21) that reported separate genome-wide association studies (GWAS) of seropositive (18,019 cases and 991,604 controls) and seronegative (8,515 cases and 1,015,471 controls) RA. One hundred and thirty-five autosomal single nucleotide polymorphisms (SNPs) that were associated with RA (either seropositive, seronegative or both) in previous GWAS of European ancestry or multi-ancestry were selected as IVs for RA (22). These IVs were used for testing the causal effect of RA as the exposure and on IPF as the outcome.…”
Section: Methodsmentioning
confidence: 99%
“…Naito et al [7] presents current fine-mapping efforts to dissect causal HLA variants of autoimmune diseases. Then, Ha et al [8], Padyukov et al [9], Kim et al [10], and Márquez et al [11] summarize recent achievements in genetics of four major autoimmune diseases of systemic lupus erythematosus, rheumatoid arthritis, multiple sclerosis, and type 1 diabetes, respectively. More than a hundred of risk variants have been massively identified for these autoimmune diseases through active international collaboration networks.…”
Section: Genetics and Functional Genetics Of Autoimmune Diseasesmentioning
confidence: 99%
“…), dysregulated immune cells (such as B cells, CD4 + T cells, etc. ), and excessive systemic inflammation contribute to RA development and progression ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%